Study of tool wear progression using nano-hybrid Cryogenic MQL in milling titanium alloy - Nurul Dayana, Mohd Noor; Musfirah, Abdul Hadi (Malaysian Tribology Society (MYTRIBOS), 2023)
Titanium is recognized for its excellent strength-toweight ratio, resistance to corrosive environments and extensively utilized in a range of industries. However, due to excellent properties of this material, it has become a difficult-to-cut material. The high heat generated during the machining process should be cooled with sufficient lubricant or coolant. High cutting temperature and stress generated when machining titanium alloy and primarily contributed to tool wear issues, resulting in various cutting tool wear behaviors. This paper investigates end milling of Ti-6Al-4V alloy using nano-hybrid cryogenic-MQL cooling system with responses to tool wear, machining time, and surface roughness. The cutting speeds of 130 and 150 m/min were selected for the experiments, with feed rates of 0.2 and 0.5 mm/rev, and the depth of cut constant at 0.5 mm using a single insert carbide tool. In this experiment, nano-hybrid cryogenic -MQL were used as the main system. The impact of cooling system and cutting parameter selection in determining optimal cutting conditions to improve tool life and tool wear was highlighted. The outcomes result shows that the cutting speed of 130 m/min and a feed rate of 0.2 mm/rev improve tool life approximately 50% and generate good surface roughness compared to other cutting parameters. To conclude, the nano-hybrid cryogenic-MQL system satisfies industry-relevant requirements, proving this approach as a viable alternative for more sustainable and environmentally friendly cooling systems.